การดัดแปรเครื่องพลาสมาโฟกัสเพื่อก่อกำเนิดรังสีเอกซ์ทรีมอัลตราไวโอเลต - ปรัชญา ตั้งจิตสมบูรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
As Extreme Ultra Violet (EUV) radiation will be widely used in future semiconductor industry and a plasma focus (PF) device has been known to be the powerful source of radiation and particles which can be easily modified to suit different applications need, therefore an interest in the modification of a PF device as an extreme ultraviolet radiation source is explored in this research. An evaluation of optimum operating parameters of a PF device for production of EUV radiation has been made by applying the corona equilibrium model and the dynamics model of plasma in a computational simulation. An interpolation method has been used to predict the relationship between the normalized current and operating pressures. Once optimum parameters are found, the parameters are used for constructing and operating of the modified PF device. The result obtained from the simulation and the experiments are then compared. Plasma diagnostics such as current probe, voltage probe and photo detector are used to determined different plasma characteristics in each experimental conditions. The results from the simulation show that the optimum parameters and conditions for EUV radiation production are when the anode length is 7.5 cm and charging voltage is 6.5 kV with the operating pressure of 2.0 mbar for 634 J PF device and the anode length is 9.0 cm and charging voltage is 8.0 kV with the operating pressure of at 2.5 mbar for 960 J PF device. Under these two optimum operating conditions, it is found that the radiation emitted from the source is in the region of extreme ultraviolet frequency, where the maximum intensity is obtained when operating with the latter conditions with operating pressure of 0.5 mbar. However, by comparing the result from the experiment and the simulation, it is found that the relationship of the operating pressure and the intensity of the optimized condition from experiment does not correspond to the simulation even though both produce EUV radiation as required.